Muslims, Schooling and the Question of Self-Segregation - Miah, S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
Drawing on empirical research amongst both Muslim schools' students and parents, this timely book examines the question of 'self-segregation' and Muslims in light of key policy developments around 'race', faith and citizenship.
Keywords: Church and education; Culture; School management and organization; School administration; Educational policy; Education and state; Child development; Religion and sociology; Religion and Education; Sociology of Culture; Administration, Organization and Leadership; Educational Policy and Politics; Early Childhood Education; Social Aspects of Religion